Efektivitas Penggunaan Lembar Evaluasi Berbasis Cerita Bergambar Terhadap Hasil Belajar IPA Kelas VII SMP Hang Tuah 1 Jakarta - Sulis Supartini (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
This study aims to determine the effectiveness of the use of evaluation sheets based on picture stories on the assessment of student learning outcomes in Natural Sciences (IPA) subjects for grade VII at SMP Hang Tuah 1 Jakarta. This study uses a quantitative descriptive approach involving 154 students from four classes (7A–7D). The evaluation instrument in the form of a short narrative accompanied by visual illustrations and contextual questions was designed based on the basic competencies of grade VII science. The results of the analysis showed that students gave a positive response to the form of evaluation used. Statistically, the average value of student learning outcomes reached 81.52, median 81.79, mode 84, and standard deviation 5.60. A total of 132 students (85.7%) achieved learning outcomes with values ​​above or equal to the Minimum Completion Criteria (KKM), which is 75. This shows that the evaluation sheet based on picture stories is not only effective in measuring learning outcomes, but also helps students understand the material more contextually and enjoyably. Student reflections strengthen these findings, where most stated that evaluation in the form of illustrated stories made them more interested, less tense when working on problems, and easier to understand concepts. Therefore, this approach can be an innovative alternative assessment in science learning.